Study of Science Visualization in Islamic Education: Study of Hadith on Picture Media - Anis Saidah; Ita Yunita; Suyudi Suyudi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This article discusses the visualization of knowledge in Islamic education, focusing on the use of visual media as a teaching aid. Historically, the Prophet Muhammad (peace be upon him) employed visual methods, such as drawing on the ground, to explain essential concepts to his companions. However, the use of images especially those depicting living beings remains controversial in Islam due to various hadiths that prohibit such practices. This study uses a qualitative approach based on literature review to examine relevant hadiths and the perspectives of both classical and contemporary scholars regarding the use of visual media in education. The findings indicate that although there are strict prohibitions on creating images of living beings, their use in educational contexts with good intentions and for instructional purposes is acceptable, provided it does not violate Islamic principles. Knowledge visualization through infographics, diagrams, and educational videos has proven effective in enhancing students’ understanding of Islamic teachings, especially in delivering abstract concepts and historical narratives. Therefore, the integration of visual media in Islamic education should be carried out wisely and selectively to support effective learning while upholding Islamic values.